The aspectual system in Singapore Hokkien - Tan, Cheryl Xue Er (2014)
This study is an in-depth analysis of the aspectual system of Singapore Hokkien, a language variety that is becoming increasingly endangered. With the aid of four native speakers, natural Singapore Hokkien speech was recorded, transcribed and analysed. The following types of grammatical marking of viewpoint aspect are discussed in this paper: Perfective, Completive, Perfect, Experiential, (Past) Habitual, Prospective, Iterative, Delimitative and Tentative. Previous literature on Singapore Hokkien and other varieties of Hokkien were also compared and contrasted against the data that have been collected for the purpose of this study. It is shown that there might be phonological and syntactical differences between Singapore Hokkien and Taiwanese. A heavy emphasis was placed on the analysis of the pat33 and ke51 particles, which were initially hypothesized to be experiential particles. However, Chappell (2001) claimed that these particles should be considered as evidential particles instead. This paper attempts to address these conflicting analyses. Verbal reduplication in Singapore Hokkien is also discussed at length, as it was observed to be a pervasive structure in Singapore Hokkien speech. It was discovered that the type of aspectual sense derived from these reduplicated structures is influenced by how extended the action associated with the verb is in time.